DISHARMONISASI KEBIJAKAN PEMBANGUNANPEMERINTAH PUSAT DAN DAERAHMENIMBULKAN GANGGUANSTABILITAS KEAMANAN DAERAH - M Ichsan Syirait Ramadhan; I Gede Sumertha; Eri R Hidayat (Jurnal Education and Development, 2022)
The paper entitled "Disharmony of Central and Regional Government Development Policies Causes Disruption of Regional Security Stability" analyzes the issue of government development policies that are not on target so that the desires and needs of the community are not met. This certainly gives birth to various conflicts as a form of community criticism so that security disturbances in various regions become disrupted. Development policies made by the center sometimes do not support the welfare of the people in the region as a result of generalizing the overall policy of the region, causing a waste of the state budget. While the problems in the area are quite complex and different. Moreover, the limited budget owned by the region requires them to optimize existing development policies. The method used by the author is qualitative descriptive with a policy theory approach in formulating a development policy. Therefore, the author recommends that the development policy that is proclaimed there needs to be intensive communication between the central and local governments, increased human resource competence in launching development policies, and bureaucratic structures that are not convoluted to the proposed regional development policy to the center. Supported by the activeness of the local government to see the problems of the community in each region in accordance with the urgency of the criteria that must be immediately accommodated and useful for the long term needs to be done. So that the potential for security disruptions from development policies can be prevented and answer the challenges of problems in existing areas.